Control of Corrosion of Copper-Alloy Condenser Tubes by Chemical Treatment - Wassan Abduallah; Nawal Jassim; Qais A.Hassan (Engineering and Technology Journal, 2012)
The present work deals with the study of the factors that affect the corrosion resistance and heat transfer resistance of treated condenser tubes by surface filming with ferrous sulfate solution. The reduction of corrosion rate on the filmed surfaces was determined under dynamic conditions using weight loss method. The variation of the corrosion rate at different exposure time and different fluid velocities of the filming solution were studied throughout the laboratory corrosion system. While the effect of surface filming on depression of heat transfer process in term of increasing the heat transfers resistance was studied throughout the laboratory thermal system. The results indicated that the filming solution reduced the corrosion rate of copper alloy to 52.7%, but the heat transfer resistance increased from 12.88 to 18.73*10-4 m2K/W. Moreover, the metallurgical investigation clearly revealed the feature and nature of the film formed on the metal surface.